Thermoelectric properties of quaternary chalcogenide Cu2ZnSnS4 synthesised by mechanical alloying. (26th May 2020) - Long, Bui Duc; Van Khanh, Nguyen; Binh, Duong Ngoc; Hai, Nguyen Hong
ABSTRACT: The quaternary chalcogenide Cu2 ZnSnS4 has emerged as a potential thermoelectric (TE) material due to its low thermal conductivity ( κ ), high Seebeck coefficient ( S ) and composition including earth-abundant, low-cost and non-toxic elements. In this work, Cu2 ZnSnS4 was synthesised from a mixture of Cu, Zn, Sn and S powders using a mechanical alloying method. As a result, Cu2 ZnSnS4 powders were formed after 16 h of milling, without additional heat treatment. After milling, the powders were heat-treated at 723 K for 24 h and then sintered by spark plasma sintering under an applied pressure of 60 MPa at 873 K for 10 min. The heat-treated Cu2 ZnSnS4 sample showed a wide-band-gap of 1.49 eV. The sintered Cu2 ZnSnS4 sample exhibited S and κ values of 170 μV K −1 and 1.06 W m −1 K −1, respectively with an electrical conductivity σ of 1240 S m −1 and a dimensionless figure of merit ( ZT ) of 0.022 at 663 K.